Efektivitas Model Pembelajaran Teams Games Tournament (TGT) terhadap Hasil Belajar Kognitif Peserta Didik di Kelas IV C SDN Keboansikep 2 pada Materi Penjumlahan dan Pengurangan Bilangan Cacah 1-100 - Aisyah, Adinda Siti; Zahrah, Ananda Amanatuz; Nikmah, Ellya Mafazatun; Zahroh, Ulfi Aminatuz; Budiyono (Journal of Contemporary Issues in Primary Education, 2025)
Mathematics is a fundamental subject that must be learned from elementary school through higher education. However, based on preliminary observations conducted at SDN Keboansikep 2, it was found that many students still struggle to understand the concepts of addition and subtraction of whole numbers 1-11 due to the use of conventional leraning models without variation. This makes students easily bored, which in turn affects their learning outcomes negatively. This study aims to determine the effectiveness of the Teams Games Tournament (TGT) learning model on the cognitive learning outcomes of Grade IV C students at SDN Keboansikep 2 on the topic of addition and subtraction of whole numbers from 1-100. The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The data collection technique used a multiple-choice cognitive test consisting of 20 items. Data were analyzed using descriptive statistics and inferential statistics, specifically the paired sample t-test and N-gain analysis. Descriptive statistics analysis showed an average pretest score of 66.54 and a posttest score of 80.19, indicating an increase of 13.654 points. Inferential statistics analysis using the paired sample t-test yielded a Sig. (2-tailed) value of 0.0001 < 0.05, indicating a difference in learning outcomes before and after the implementation of the TGT model. The N-gain results showed an average score of 0.475 (moderate) and a percentage of 47.52% (fairly effective). Based on these findings, it can be concluded that the TGT learning model resulted a difference and is fairly effective in the cognitive learning outcomes of Grade IV C students at SDN Keboansikep 2 on topic of addition and subtraction of whole numbers 1-100. It is recommended that educators consistently implement the TGT learning model in elementary school classrooms.